Effects of tri‐frequency ultrasound‐ethanol pretreatment combined with infrared convection drying on the quality properties and drying characteristics of scallion stalk. (18th November 2020) - Zhou, Cunshan; Wang, Zezhi; Wang, Xule; Yagoub, Abu EA; Ma, Haile; Sun, Yanhui; Yu, Xiaojie
Abstract: BACKGROUND: Having short drying time and attractive product quality are important in fruit and vegetable dehydration processing. In this work, tri‐frequency (20, 40 and 60 kHz) ultrasound‐ethanol pretreatment, ultrasound‐water pretreatment and ethanol pretreatment were employed before infrared convection drying (ICD) of scallion stalks, which was aimed at improving the drying process and quality of the end products. The mass transfer, drying characteristics (moisture ratio and drying rate and quality properties of scallion (rehydration, color, flavor, optical microscope image, moisture distribution and microbiological quality) were analyzed. RESULTS: All pretreatments have decreased the drying time by 33.34–83.34% compared to the control, while ultrasound‐ethanol pretreatment provided the highest time reduction (83.34%). The reason is that the volatility of ethanol have replaced air in the tissue, which produced a better osmotic dehydration effect and the cavitation effect of ultrasound changed the cell function of the material, so that the food tissue was rapidly compressed and expanded, resulting in damage to the cell structure. Ultrasonic‐ethanol pretreatment has greatly reduced the water loss and dry matter of fresh scallion, improved the rehydration effect of dried scallion, better retained the color and flavor of scallion and effectively reduced the microbiological quality of the scallion. CONCLUSION: The tri‐frequency ultrasound‐ethanol pretreatment has effectively improved the drying process and quality characteristics of the dried scallion. Therefore, this research has a great contribution to the drying technology, as evident in the remarkable reduction in drying time and the improvement in the quality of the end product. © 2020 Society of Chemical Industry